PENGARUH BUDAYA SISTEMATIS REKRUITMEN DAN PENEMPATAN KERJA TERHADAP KINERJA KARYAWAN PADA PT.POS INDONESIA CABANG SIBOLGA - Yanti Feronika Siregar; Nelly A. Sinaga; Heriyawan Hutagalung (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
The purpose of this study was to determine and analyze the effect of systematic recruitment and job placement on employee performance at PT. Sibolga branch of Pos Indonesia. The type of research used is descriptive. The sample in this study were employees at PT. Pos Indonesia sibolga branch, totaling 22 people. The data used is secondary data. Primary data was collected using a questionnaire. The analytical method used is descriptive analysis method and statistical analysis method, namely by multiple linear regression analysis where the data processing uses the SPSS 25 program for windows. The use of regression analysis is intended to see the influence of the variables of the recruitment and job placement system together. The results of the study show that the variables of the recruitment and job placement system have a joint effect on employee performance at PT. Sibolga branch of Pos Indonesia. From the calculation of the coefficient of determination obtained by 78.96%. This means that what happens to the dependent variable (employee performance) is 78.9%. It is determined by the independent variables (systematic recruitment and work placement) and the remaining 21.1% is determined by the factor other things that are not discussed by the author, such as variables and human resources, communication and others. This shows that the recruitment system variable is the dominant variable of the job placement variable and has a direct effect on employee performance.